2016
DOI: 10.1038/srep27696
|View full text |Cite
|
Sign up to set email alerts
|

Targeting MCL-1/BCL-XL Forestalls the Acquisition of Resistance to ABT-199 in Acute Myeloid Leukemia

Abstract: ABT-199, a potent and selective small-molecule antagonist of BCL-2, is being clinically vetted as pharmacotherapy for the treatment of acute myeloid leukemia (AML). However, given that prolonged monotherapy tends to beget resistance, we sought to investigate the means by which resistance to ABT-199 might arise in AML and the extent to which those mechanisms might be preempted. Here we used a pathway-activating genetic screen to nominate MCL-1 and BCL-XL as potential nodes of resistance. We then characterized a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
115
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(121 citation statements)
references
References 27 publications
6
115
0
Order By: Relevance
“…Thus, our findings may be similar to those found by Klanova et al in diffuse large B- cell lymphoma, where the combination of homoharringtonine (parent compound of omacetaxine) and ABT-199 was active 52 . This group hypothesized that the efficacy of combination treatment is due to targeting both BCL-2 and MCL-1 53 , 54 . We confirmed decreased MCL-1 levels upon treatment with omacetaxine in the MDS-L cell line (Supplementary fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, our findings may be similar to those found by Klanova et al in diffuse large B- cell lymphoma, where the combination of homoharringtonine (parent compound of omacetaxine) and ABT-199 was active 52 . This group hypothesized that the efficacy of combination treatment is due to targeting both BCL-2 and MCL-1 53 , 54 . We confirmed decreased MCL-1 levels upon treatment with omacetaxine in the MDS-L cell line (Supplementary fig.…”
Section: Resultsmentioning
confidence: 99%
“…[5] In a recent report, investigators characterized a panel of venetoclax-resistant myeloid leukemia cell lines derived through chronic exposure to venetoclax and found that acquired drug resistance was indeed driven by the up-regulation of MCL-1 and BCL-X L . [102] Interestingly, not only could the resistant AML cell lines be re-sensitized to venetoclax by targeting MCL-1 and BCL-X L , pre-emptively targeting one or both of the latter could actually delay or forestall the acquisition of venetoclax resistance. [102] These findings have obvious implications for selection of initial therapy for AML.…”
Section: Major Determinants Of Venetoclax Resistance: Mcl-1 and Bcl-xlmentioning
confidence: 99%
“…[102] Interestingly, not only could the resistant AML cell lines be re-sensitized to venetoclax by targeting MCL-1 and BCL-X L , pre-emptively targeting one or both of the latter could actually delay or forestall the acquisition of venetoclax resistance. [102] These findings have obvious implications for selection of initial therapy for AML.…”
Section: Major Determinants Of Venetoclax Resistance: Mcl-1 and Bcl-xlmentioning
confidence: 99%
“…Among these, 39% of the pooled and 29% of the clonal populations could be resensitized to MAPK inhibition through shRNA mediated knockdown of Notch1. Similarly, we validated the finding that MCL-1 and BCL-X L up-regulation can drive resistance to the potential to be used to address many other questions in selective BCL-2 inhibitor ABT-199 (venetoclax) in acute myeloid leukemia (AML) by demonstrating the resensitization of cells with acquired resistance through knockdown or small molecule inhibition of these candidate resistance proteins [ 48 ]. Finally, we validated Ras effector pathways PI3K and MAPK as drivers of acquired resistance to JAK inhibitors in JAK2 mutant cells using a similar approach in cells with acquired JAKi resistance [ 47 ].…”
Section: Approachmentioning
confidence: 73%